Thickness Effect on Permeance of CO2/CH4 Gases in CA Coated PVDF Composite Membranes. Issue 2 (3rd April 2021) - Raza, Ayesha; Yousaf, Muhammad Fahad; Farrukh, Sarah; Hussain, Arshad
Abstract : The aim of this work is to study the effect of membrane thickness with respect to gas permeance and tensile strength. The influence of membrane thickness on gas permeation has received little attention to date. Single layer flat sheet membrane with average thickness of 25 μm and dual layer composite membranes with variable thickness of skin layer were fabricated by coating CA/ PEG selective layer on the polyvinylidene fluoride porous support. Permeation experiments were performed with CO2 and CH4 which revealed that permeance of CO2 was pronounced compared to CH4 . Highest permeance of 0.87 gas permeation unit (GPU) was obtained at 4 bar with 19.4 μm skin layer. Fourier transform infra-red spectroscopy was used to study the existence of different functional groups in the membranes. Strength of the membranes was analyzed using tensile testing machine. Scanning electron microscopy was used to study the surface structure and morphology. It was found that by reducing the membrane thickness, the permeance of CO2 and CH4 increased without compromising on membrane strength. GRAPHICAL ABSTRACT: UF0001